Anti-inflammatory meroterpenoids from the mangrove endophytic fungus Talaromyces amestolkiae YX1. (February 2018) - Chen, Senhua; Ding, Meng; Liu, Weiyang; Huang, Xishan; Liu, Zhaoming; Lu, Yongjun; Liu, Hongju; She, Zhigang
Abstract: Four previously undescribed meroterpenoids, amestolkolides A−D, along with three known compounds were isolated from the mangrove endophytic fungus Talaromyces amestolkiae YX1 cultured on wheat solid-substrate medium culture. Their structures were elucidated by a combination of spectroscopic analyses. The absolute configurations of amestolkolides B and C, and purpurogenolide E were determined by single-crystal X-ray diffraction using Cu K α radiation, and those of amestolkolides A and D were elucidated on the basis of experimental and calculated electronic circular dichroism spectra. The absolute configuration of amestolkolides A-D, and purpurogenolide E (9 R ) at C-9 was different from that of analogues (9 S ) in references, so that their plausible and distinct biosynthetic pathways were proposed. Amestolkolide B showed strong anti-inflammatory activity in vitro by inhibiting nitric oxide (NO) production in lipopolysaccharide activated in RAW264.7 cells with IC50 value of 1.6 ± 0.1 μ M. Graphical abstract: Four previously undescribed meroterpenoids, amestolkolides A−D, were isolated from the mangrove endophytic fungus Talaromyces amestolkiae YX1. Amestolkolide B showed strong anti-inflammatory activity with IC50 value of 1.6 ± 0.1 μ M. Highlights: Four previously undescribed meroterpenoids, amestolkolides A−D were isolated from Talaromyces amestolkiae YX1. Their plausible and distinct biosynthetic pathways were proposed. This series of meroterpenoids were firstly isolated from the fungi in the genus Talaromyces. Amestolkolides B showed strong anti-inflammatory activity with IC50 values of 1.6 ± 0.1 μ M in vitro.